Clinical Classification and Collateral Circulation in Chronic Cerebrospinal Venous Insufficiency - Wang, Zhongao; Ding, Jiayue; Bai, Chaobo; Ding, Yuchuan; Ji, Xunming; Meng, Ran (Frontiers in Neurology, 2020)
Background: As an indispensable part of the cerebral venous system, the extracranial cerebrospinal venous system is not fully recognized. This study aimed to analyze the clinical classification and imaging characteristics of chronic cerebrospinal venous insufficiency (CCSVI) quantitatively. Methods: A total of 128 patients, who were diagnosed as CCSVI by jugular ultrasound and contrast-enhanced magnetic resonance venography (CE-MRV), were enrolled from May 2018 through May 2019. For the patients with possible extraluminal compression, computed tomography venography (CTV) was applied to estimate the degree of internal jugular venous stenosis (IJVS) and rank the vertebral venous collateral circulation. Results: The causes of extraluminal compression induced IJVS included osseous compression (78.95%), carotid artery (24.21%), sternocleidomastoid muscle (5.79%), swollen lymph node (1.05%), and unknown reasons (5.26%). The subtypes of non-compression CCSVI included the high jugular bulb (77.27%), fenestration of the internal jugular vein (IJV) (7.27%), internal jugular phlebectasia (2.73%), tortuous IJV (0.91%), IJV thrombosis (14.55%), and elongated venous valves with/without erythrocyte aggregation (13.64%). For extraluminal compression induced IJVS, the ratio of severe vertebral venous expansion was higher in the severe IJVS group than that in the mild IJVS group (p < 0.001). The IJVS degree was higher in the severe vertebral venous expansion group than in the mild vertebral venous expansion group (p < 0.001). Conclusions: A multimodal diagnostic system is necessary to improve the diagnostic accuracy of CCSVI. The vertebral venous system is an important collateral circulation for CCSVI, which may be a promising indicator for evaluating IJVS degree.